Russia in the era of NEP : explorations in Soviet society and culture - Fitzpatrick, Sheila; Rabinowitch, Alexander; Stites, Richard (Bloomington : Indiana University Press, 1991)
Bibliotheek François Vercammen
Engels
Monografie